If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6k-4+3k=21
We move all terms to the left:
-6k-4+3k-(21)=0
We add all the numbers together, and all the variables
-3k-25=0
We move all terms containing k to the left, all other terms to the right
-3k=25
k=25/-3
k=-8+1/3
| 13u=12+9u | | 6+10k=2(-4k-6)= | | 0.5x+4=5x-32 | | 3e—6=30 | | 1.50/n=2.33 | | 9x-1+3x+18=3x-4 | | x-3/5=x+3/15 | | r−3=14 | | 8/1x-4=6 | | 1.5(d+3.5)=2.4 | | -2(1+2x)=10 | | 7x-53=360 | | −x+4=23 | | 2s=3s+1 | | 4h+-5h-4=-8 | | (4x+12)=7x | | 5(-2-x)=-7(2x+4) | | 37+s=80÷2= | | 4x+12=x(2+6) | | 10p-3p-5=16 | | 3(6-4x)=-2(2x-17) | | 8/1x-2=3 | | 4(j+8)=-16 | | -4(5x-9)=6(2x+5) | | 4x−2(x−3)=−4+5x−8 | | 4x+2+75+63=180 | | 8f+9f=32 | | -6x^2-18+60=0 | | 8/1x-2=6 | | 1/2(6x+10)=13 | | 4x+5-2x-2=3x-3×-3 | | 1x–5=5–9x |